2024
DOI: 10.3390/ijms25041976
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights in Prolactin Signaling and Ovulatory Function

Dariusz Szukiewicz

Abstract: Prolactin (PRL) is a pleiotropic hormone released from lactotrophic cells of the anterior pituitary gland that also originates from extrapituitary sources and plays an important role in regulating lactation in mammals, as well as other actions. Acting in an endocrine and paracrine/autocrine manner, PRL regulates the hypothalamic–pituitary–ovarian axis, thus influencing the maturation of ovarian follicles and ovulation. This review provides a detailed discussion of the current knowledge on the role of PRL in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 311 publications
(407 reference statements)
0
0
0
Order By: Relevance
“…Endocrine pathways play an essential role in the menstrual cycle [44], throughout which hormone levels fluctuate [45], regulating estrus production [46] and ovulation [47]. Our study showed that PRL inhibition significantly increased the concentrations of GnRH, FSH, and E2 as well as the number of small follicles in the proestrus stage and increased the concentrations of GnRH and E2 in the estrus stage.…”
Section: Effect Of Prl On the Secretion Of Related Reproductive Hormonesmentioning
confidence: 52%
See 1 more Smart Citation
“…Endocrine pathways play an essential role in the menstrual cycle [44], throughout which hormone levels fluctuate [45], regulating estrus production [46] and ovulation [47]. Our study showed that PRL inhibition significantly increased the concentrations of GnRH, FSH, and E2 as well as the number of small follicles in the proestrus stage and increased the concentrations of GnRH and E2 in the estrus stage.…”
Section: Effect Of Prl On the Secretion Of Related Reproductive Hormonesmentioning
confidence: 52%
“…Our study showed that PRL inhibition significantly increased the concentrations of GnRH, FSH, and E2 as well as the number of small follicles in the proestrus stage and increased the concentrations of GnRH and E2 in the estrus stage. A high PRL concentration suppresses the hypothalamic gonadotropin-releasing hormone, which plays a pivotal role in reproduction by stimulating the synthesis and secretion of LH and FSH [47]. Upon FSH stimulation, a cohort of small antral follicles begins the gonadotropin-dependent development phase of recruited follicles [48].…”
Section: Effect Of Prl On the Secretion Of Related Reproductive Hormonesmentioning
confidence: 99%